Inflammatory bowel disease and venous thromboembolism during pregnancy and the postpartum period. (24th February 2017) - Hansen, A. T.; Erichsen, R.; Horváth‐Puhó, E.; Sørensen, H. T.
Abstract : Essentials Risk of pregnancy‐related venous thromboembolism may be increased in inflammatory bowel disease. We performed a study on inflammatory bowel disease and pregnancy‐related venous thromboembolism. Inflammatory bowel disease is a risk factor for pregnancy‐related venous thromboembolism. Proper disease control before conception is pivotal to avoid venous thromboembolism. Summary: Background: The incidence of inflammatory bowel disease (IBD) increases, and thus is more common, in pregnant women. IBD is a risk factor for venous thromboembolism (VTE) but it is not clear whether IBD predisposes women to an excess risk of VTE during pregnancy and the postpartum period. Methods: This was a nationwide population‐based cohort study of all deliveries during 1980–2013 in Denmark, using data from two nationwide health registries: the Danish National Patient Registry and the Medical Birth Registry. We computed incidence rates (IRs) per 1000 person‐years, and crude and adjusted relative risks (RRs) with 95% confidence intervals (CIs) for VTE during pregnancy and the first 12 postpartum weeks in women with and without IBD. Results: We included 1 046 754 women with 1 978 701 deliveries. We identified 3465 VTE events during pregnancy and 1302 VTE events postpartum. The IR for VTE during pregnancy was 4.20 (95% CI, 2.83–5.58) in IBD patients and 2.41 (95% CI, 2.33–2.50) in women without IBD, corresponding to an RR of 1.72 (95% CI, 1.22–2.43). Adjustment for maternal age and smoking (pregnancies during 1991–2013) yielded an adjusted RR of 1.67 (95% CI, 1.15–2.41). IBD flare was associated with an RR of 2.64 (95% CI, 1.69–4.14) for VTE during pregnancy. The IR for postpartum VTE was 7.03 (95% CI, 3.87–10.20) among IBD patients and 2.88 (95% CI, 2.72–3.04) in women without IBD, corresponding to an adjusted RR of 2.10 (95% CI, 1.33–3.30). Conclusions: IBD is a risk factor for VTE during pregnancy and postpartum.